Vowel Inherent Spectral Change 2012
DOI: 10.1007/978-3-642-14209-3_4
|View full text |Cite
|
Sign up to set email alerts
|

Vowel Inherent Spectral Change in the Vowels of North American English

Abstract: Nearey and Assmann (1986) coined the term 'vowel inherent spectral change' (VISC) to refer to change in spectral properties inherent to the phonetic specification of vowels. Although such change includes the relatively large formant changes associated with acknowledged diphthongs, the term was explicitly intended to include reliable (but possibly more subtle) spectral change associated with vowel categories of North American English typically regarded as monophthongs. This chapter reviews statistical and graph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 44 publications
0
18
0
1
Order By: Relevance
“…Phonetic research has shown that several vowels traditionally classified as monophthongs show systematic patterns of formant movement, apparently reflecting inherent properties of the vowels themselves (Nearey, 2013). The traditional opinion is that Spanish /a, e, o/ are monophthongs, i.e.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Phonetic research has shown that several vowels traditionally classified as monophthongs show systematic patterns of formant movement, apparently reflecting inherent properties of the vowels themselves (Nearey, 2013). The traditional opinion is that Spanish /a, e, o/ are monophthongs, i.e.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…예를 들어, Yang(1996) (Hillenbrand et al, 1995;Nearey, 2013;Haddican, 2013). Hillenbrand et al(1995)는 영어 단모음 /ae, ε/의 안정구간 …”
unclassified
“…It is well established that formant movement inherent to the vowel (VISC) and the effects of coarticulation are key contributors to contextrelated effects (Nearey, 2013) and further study is required using additional talkers to model these effects for individual vowels.…”
Section: Discussionmentioning
confidence: 99%
“…While duration and temporal variability have been studied in a variety of contexts, the study of context effects on formant movement within the vowel (vowel inherent spectral change, or VISC; Nearey and Assmann, 1986;Nearey, 2013;Assmann et al, 2013) has received less attention. A limitation of existing research on VISC has been that most studies have examined patterns of formant movement in a limited number of talkers or exclusively in adults rather than in children.…”
Section: Introductionmentioning
confidence: 99%